Evaluation of the Adiwiyata Award Program to Form an Environmental Care Movement at SMP Negeri 3 Candi, Sidoarjo Regency - Muhammad Bagus Fajar Mukti; Sri Roekminiati; Aris Sunarya; Kristiyan Dwijosusilo (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to evaluate the Adiwiyata Award Program in forming an environmental care movement at SMP Negeri 3 Candi, Sidoarjo Regency. This study uses an evaluation approach with the CIPP (Context, Input, Process, Product) model from Daniel Stufflebeam. Data were collected through observation, interviews, and documentation related to program implementation. Each element was evaluated to assess the suitability between objectives, resources, implementation, and impacts generated. Data were analyzed descriptively. The results showed that the program was implemented effectively and in accordance with established procedures, with activities that met the criteria for achieving Adiwiyata School status. The Context element identifies that the program is based on the school's vision, mission, and objectives to increase environmental awareness. The Input element evaluates institutional readiness, including adequate human resources, budget, and infrastructure. The Process element highlights activities such as the implementation of "Clean Friday" and the integration of environmental learning involving the entire school community. The Product element shows the results in the form of a green and comfortable environment, as well as changes in student behavior who practice environmentally friendly habits, such as organic and inorganic waste management